Controlling Hierarchy in Solution‐processed Polymer Solar Cells Based on Crosslinked P3HT. Issue 1 (7th August 2012) - Tao, Chen; Aljada, Muhsen; Shaw, Paul E.; Lee, Kwan H.; Cavaye, Hamish; Balfour, Michael N.; Borthwick, Robert J.; James, Michael; Burn, Paul L.; Gentle, Ian R.; Meredith, Paul
Abstract Understanding and controlling the morphology of donor/acceptor blends is critical for the development of solution processable organic solar cells. By crosslinking a poly(3‐n‐hexylthiophene‐2, 5‐diyl) (P3HT) film we have been able to spin‐coat [6, 6]‐phenyl‐C61‐butyric acid methyl ester (PCBM) onto the film to form a structure that is close to a bilayer, thus creating an ideal platform for investigating interdiffusion in this model system. Neutron reflectometry (NR) demonstrates that without any thermal treatment a smaller amount of PCBM percolates throughout the crosslinked P3HT when compared to a non‐crosslinked P3HT film. Using time‐resolved NR we also show thermal annealing increases the rate of diffusion, resulting in a near‐uniform distribution of PCBM throughout the polymer film. XPS measurements confirm the presence of both P3HT and PCBM at the annealed film's surface indicating that the two components are intermixed. Photovoltaic devices fabricated using this bilayer approach and suitable annealing conditions yielded comparable power conversion efficiencies to bulk heterojunction devices made from the same materials. The crosslinking procedure has also enabled the formation of patterned P3HT films by photolithography. Pillars with feature sizes down to 2 μm were produced and after subsequent deposition of PCBM and thermal annealing devices with efficiencies of up to 1.4% were produced.